Microsurgical reconstruction of the isolated columellar defect with a prelaminated radial forearm free flap. A case report and a review of the literature. Issue 2 (21st May 2019) - Maruccia, Michele; Elia, Rossella; Nacchiero, Eleonora; Giudice, Giuseppe
Abstract: The columella is one of the smallest subunits of the nose, but the loss of this structure has important aesthetic and structural implications. Few papers in literature present microsurgical techniques for the reconstruction of an isolated columellar defect. This report describes the use of a prelaminated radial forearm free flap (RFFF) for the reconstruction of an isolated columellar defect and reviews the current literature. A 45‐year‐old woman presented to our Unit with a history of palate squamous cell carcinoma and severe nasal deformity with an almost complete loss of the columella. A prelaminated RFFF with the fifth rib was used for a two‐staged reconstruction of the isolated columellar defect. The radial pedicle was anastomosed to the facial vessels and the postoperative course was uneventful. Complete survival of the flap was achieved and, 10 months postoperatively, the patient had bilateral nasal patency, with an increased tip projection and a good aesthetic result. A prelaminated RFFF can be considered a valuable reconstructive option in cases of a large composite defect of the columella and limited availability of adjacent tissues.